(untitled) (Journal of the College of Basic Education, 2022)
Many educator in different spots of Arab Nations explain the defect behind the process of teaching saying that the lack and the absence of scientific programs and modern ways affect directly on teaching so they claim to modernize ways that help student and teachers to improve their level adequately . The important of research . The study stresses at shedding the light on the importance of teacher’s role in the process of teaching . It paves the way to take into account the basic duties regarding the employment of theoretical aspects in academic preparation ; to put it into practice and make use of it in future lessons . The research aim . The study aims at knowing the level of students in historical and geographical departments and how they exploit teaching skills . And whatever this level reaches its acceptable educational medium or not . The place of the research . The present research takes its place among students in the fourth stage in college of education and human sciences at Al – Anbar . Research problem : Many educators in various parts of the Arab world have identified a clear deficiency in the professional performance of teachers, and attributed the reason for this to the insufficiency of the programs and methods adopted in the preparation, and called for finding more advanced methods that would enable the student/applicant to perform teaching skills better than it is. research importance : It clarifies the role that practical education plays in teacher preparation programs, as well as allowing the student/applicant to practice the basic tasks of the teaching process by employing the theoretical aspects he received during academic preparation and translating them into an applied reality that helps him in exercising the role of the future teacher. Search objective: The research aims to know the level of mastery of students/applicants in the departments of history and geography from the skills of classroom teaching? And whether this level reaches the educationally acceptable medium or not. research community : The current research community is represented by students of the fourth stage in the College of Education for Human Sciences - University of Anbar, and their number is (252) male and female students, and the researcher chose (100). Conclusions: In light of the research results, the researcher reached the following conclusions: 1- Adopting the objective observation form is an effective means in evaluating the performance of students/applicants of teaching competencies during the period of their application in schools. 2- The evaluation of the performance of the students/applicants of the teaching competencies was below the educationally acceptable average (75%), with the exception of only six paragraphs. The estimate of their performance was above the educationally acceptable average. 3- The obvious deficiency in the preparation programs in the College of Education for Human Sciences, as it does not keep pace with recent developments in the field of observation, application and teaching methods. Modern in the field of observation, application and teaching methods. Second: Recommendations: In light of the results and conclusions reached by the researcher, he recommended the following: 1- That we put the College of Education into a guide that explains everything related to viewing and application, from which the responsibility of the college administration, the school administration and the supervisors of students/applicants are determined. 2- Not to use supervisors who are not specialized in education. 3- The specialized supervisors in the education directorates have benefited from the objective observation form for the current research in evaluating teachers’ performance of teaching competencies and training them on how to use them. Third: Suggestions: To complete this study, the researcher suggests the following: 1- Conducting a study similar to the current study on students/applicants to other college departments to compare the results of this study with its results so that the conclusions and recommendations about the preparation programs are more objective and accurate. 2- Conducting a study similar to the current study to identify the level of use of teaching competencies other than those discussed in this research. 3- Conducting an empirical study to identify the effect of using modern strategies in training students/applicants on teaching competencies such as yellowing strategies